Vitamin B1 and sepsis: a prospective single-center study - Yan, Wenbo; Ma, Yushu; Yang, Jingping; Wang, Hongyan; Li, Tiewei (Frontiers in Nutrition, 2026)
PurposeVitamin B1 (VB1), an essential coenzyme in cellular energy metabolism, is postulated to modulate clinical outcomes in sepsis. However, the relationship between VB1 and sepsis remains inadequately explored both domestically and internationally, and its potential clinical value remains unclear. Therefore, this study aims to investigate the association between VB1 deficiency and the severity of sepsis, and to evaluate the potential clinical utility of VB1 in ameliorating sepsis-induced organ injury and coagulation dysfunction.MethodsA total of 67 patients from Inner Mongolia Baogang Hospital were enrolled in this study. Among them, 41 were assigned to the sepsis group (clinically diagnosed with sepsis), and the remaining 26 comprised the control group (patients with ordinary pneumonia who did not meet the clinical diagnostic criteria for sepsis). Serum VB1 levels were measured using ultra-high-performance liquid chromatography–tandem mass spectrometry from peripheral blood samples. Clinical and laboratory data were obtained from electronic medical records. Multivariate logistic regression analysis was employed to assess the potential of VB1 as an independent biomarker for sepsis. All statistical analyses were performed using SPSS version 27.0.ResultsThe sepsis group exhibited significantly lower VB1 levels than the control group (p < 0.001). Further analysis revealed a significantly higher proportion of sepsis patients in the VB1 deficiency group compared to the control group, whereas the VB1 sufficiency group showed a significantly lower proportion of sepsis patients (p < 0.001). Correlation analysis demonstrated significant negative correlations between VB1 levels and sequential organ failure assessment scores, procalcitonin, D-dimer, creatinine, and cardiac troponin I, and positively correlated with albumin. Multivariable logistic regression analysis revealed that when VB1 was analyzed as a continuous variable, a high VB1 level was independently associated with a low prevalence of sepsis (OR = 0.127, 95% CI: 0.022–0.744, p = 0.022).ConclusionVB1 levels exhibit an inverse association with key inflammatory biomarkers in patients with sepsis, and reduced VB1 concentration is independently associated with a higher prevalence of sepsis.